NOMINAL IMMISERIZING GROWTH: TECHNOLOGICAL PROGRESS, DEFLATION, AND FOREIGN CURRENCY ACCUMULATION - Fujita, Yasunori (International Journal of Research -GRANTHAALAYAH, 2026)
This paper develops a simple domestic macroeconomic model to examine how technological progress can generate immiserizing growth in nominal terms. While productivity improvements typically raise real output, the model shows that technological progress may sharply reduce prices when the price elasticity of demand is sufficiently low. As a result, the GDP deflator declines and nominal GDP falls over time despite continuous growth in real output. The analysis further demonstrates that declining nominal income leads to an expansion of foreign currency transactions, as domestic expenditure on goods decreases. By explicitly focusing on nominal GDP and price dynamics rather than real output alone, this paper provides a new interpretation of immiserizing growth and highlights an overlooked channel linking technological progress, deflation, and foreign currency accumulation.